Appropriability and the retrieval of knowledge after spillovers - ALNUAIMI, Tufool (Institutional Knowledge at Singapore Management University, 2016)
Firms create and capture value through innovation. In technology-driven firms, there has been an explicit emphasis on appropriability through imitation deterrence and cumulative inventions that build on prior firm innovation. We introduce systematic empirical evidence for a third mechanism of appropriability namely, knowledge retrieval, which is defined as the re-absorption of previously spilled knowledge. We extend previous studies which consider technological complexity and organizational coupling as predictors of appropriability by examining their impact on knowledge retrieval. We find that technological complexity has a curvilinear relationship with retrieval while organizational coupling has a negative relationship. We discuss the implications of these findings for theories of absorptive capacity, organizational design and appropriability of innovation.